Studying the Bound State of the BK¯ System in the Bethe-Salpeter Formalism. (4th March 2019) - Wang, Zhen-Yang; Qi, Jing-Juan; Guo, Xin-Heng
Abstract : In this work, we study theB K ¯ molecule in the Bethe-Salpeter (BS) equation approach. With the kernel containing one-particle-exchange diagrams and introducing two different form factors (monopole form factor and dipole form factor) in the vertex, we solve the BS equation numerically in the covariant instantaneous approximation. We investigate the isoscalar and isovectorB K ¯ systems, and we find thatX 5568 cannot be aB K ¯ molecule.